2016
DOI: 10.1007/s12551-016-0205-y
|View full text |Cite
|
Sign up to set email alerts
|

DNA supercoiling is a fundamental regulatory principle in the control of bacterial gene expression

Abstract: Although it has become routine to consider DNA in terms of its role as a carrier of genetic information, it is also an important contributor to the control of gene expression. This regulatory principle arises from its structural properties. DNA is maintained in an underwound state in most bacterial cells and this has important implications both for DNA storage in the nucleoid and for the expression of genetic information. Underwinding of the DNA through reduction in its linking number potentially imparts energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 170 publications
1
74
0
Order By: Relevance
“…In addition to RNA-based or transcription-factor-based gene regulation in bacteria, environmentally triggered changes in DNA-topology can play a decisive role in setting the transcriptional activity of promoters (Wang and Syvanen, 1992;Dorman, 1996;Travers and Muskhelishvili, 2005;Dorman and Corcoran, 2009;Dorman and Dorman, 2016). Such changes in DNA topology trigger genomewide changes in transcriptional profile (Cheung et al, 2003;Lal et al, 2016) and both increases and decreases in supercoiling seem to act as a kind of second messenger transmitting information about fluctuations in the environment to regulatory networks in the cell (Hatfield and Benham, 2002;Peter et al, 2004;Dorman and Dorman, 2016;Lal et al, 2016). Rises in the environmental osmolarity are one of the well known cues that lead to increases in negative superhelicity, both in Gram-negative and Grampositive bacteria (Higgins et al, 1988;Krispin and Allmansberger, 1995;Alice and Sanchez-Rivas, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to RNA-based or transcription-factor-based gene regulation in bacteria, environmentally triggered changes in DNA-topology can play a decisive role in setting the transcriptional activity of promoters (Wang and Syvanen, 1992;Dorman, 1996;Travers and Muskhelishvili, 2005;Dorman and Corcoran, 2009;Dorman and Dorman, 2016). Such changes in DNA topology trigger genomewide changes in transcriptional profile (Cheung et al, 2003;Lal et al, 2016) and both increases and decreases in supercoiling seem to act as a kind of second messenger transmitting information about fluctuations in the environment to regulatory networks in the cell (Hatfield and Benham, 2002;Peter et al, 2004;Dorman and Dorman, 2016;Lal et al, 2016). Rises in the environmental osmolarity are one of the well known cues that lead to increases in negative superhelicity, both in Gram-negative and Grampositive bacteria (Higgins et al, 1988;Krispin and Allmansberger, 1995;Alice and Sanchez-Rivas, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatics analysis showed that this promoter design is strictly conserved among members of Bacilli and Halobacilli predicted to synthesize proline as an osmostress protectant. Collectively, our data suggests that the proHJ promoter belongs to a group of promoters that are sensitive to changes in DNA topology and might use these alterations to convert environmental changes in osmolarity into changes in transcriptional activity (Higgins et al ., ; Wang and Syvanen, ; Jordi et al ., ; Dorman and Dorman, ). Furthermore, through targeted quantitative proteomics of osmotically non‐stressed and stressed cells, we have asked whether the amounts of the ProA protein jointly used by the anabolic and osmostress‐adaptive proline synthesis routes of B. subtilis (Fig.…”
Section: Introductionmentioning
confidence: 98%
“…Thus, shifts in the ratio of the intracellular concentration of ATP to ADP in favour of ADP result in a global shift in DNA topology toward a more relaxed template. This happens when metabolic flux rates in the cell decline, leading to an extension in doubling time and eventually, the onset of stationary phase (Conter et al ., ; Dorman et al ., ; Dorman and Dorman, ). Topological shifts in DNA shape throughout the growth cycle present to DNA binding proteins the same sets of binding site sequences in a variety of conformations.…”
Section: The Ompr Whth Regulatory Proteinmentioning
confidence: 98%
“…The leuO gene is regulated positively by its own product and, at least in E. coli , by another wHTH protein called LrhA (Breddermann and Schnetz, ). The leuO gene is located within an unusual regulatory cascade that involves transcription activation by locally generated changes in DNA negative supercoiling: a promoter relay (Fang and Wu, ; Dorman and Dorman, ). The LeuO protein relieves H‐NS‐mediated repression and cooperates with DNA topological dynamism in this relay to regulate transcription of genes involved in branched chain amino acid synthesis (Chen et al ., ).…”
Section: Other Whth Proteins and V Cholerae And S Typhimurium Pathomentioning
confidence: 99%
“…One may speculate that secondary structures of the promoter bring these two regulators in close proximity to the SigB consensus motif, allowing them to interfere with SigB binding. It is well known that DNA structural elements like supercoiling are involved in the control of bacterial gene expression (Dorman and Dorman, 2016), and cap expression was indeed shown to be supercoiling sensitive (Schröder et al, 2014).…”
Section: Cap Expression Is Modified By Upstream Siga Promoter and Repmentioning
confidence: 99%